Screening for metabolic syndrome in patients newly diagnosed with hypothyroidism to identify the compounding effect on cardiovascular disease risk - Mohammed, Arslan; Manohar, Suchitra M.; Kumari M., Kusuma; Sachan, Alok (International Journal of Research in Medical Sciences, 2026)
Background: Lowered thyroid hormones and elevated thyroid stimulating hormone (TSH) levels of hypothyroid state are found to be associated with metabolic changes encompassing components of metabolic syndrome (MetS). Both hypothyroidism and MetS are individually associated with risk of cardiovascular disease (CVD). The presence of MetS can have a compounding effect on the CVD risk in hypothyroidism. Methods: A case-control cross sectional study was done in 30 newly diagnosed hypothyroid cases and 30 healthy controls. Waist circumference (WC), height, weight and blood pressure (BP) were recorded; fasting venous blood sample was collected for thyroid function tests, glucose, lipids and insulin. Insulin resistance as homeostasis model assessment for insulin resistance (HOMA-IR) and body mass index (BMI) was calculated. Comparison of means and correlation analysis was done using SPSS version 22. Results: Higher BMI (p=0.001), WC (p<0.001), BP (systolic p=0.039; diastolic p<0.001), total cholesterol (TC) (p=0.001), triglycerides (TGL) (p<0.001), very low-density lipoproteins (p<0.001) and fasting plasma glucose (FPG) levels (p<0.001) were observed in hypothyroid subjects. MetS was found in 11 of the 22 females and three of the eight male subjects with hypothyroidism. Presence of individual components of MetS in hypothyroidism was WC (90%), TGLs (83.3%) and high density lipoprotein (HDL) (73.3%). All female subjects in both groups had higher WC. Among female controls, two had MetS. Hypothyroidism was found to associated with components of MetS. Conclusions: Hypothyroidism associated metabolic changes can lead to the development of MetS. Targeted therapeutic interventions and life style modifications can attenuate compounding effect on of MetS on CVD risk in hypothyroidism.